Proceedings of the First International Conference on Data Engineering and Machine Intelligence ICDEMI 2023 - Kumar, S. Rakesh; Kadry, Seifedine; Gayathri, N.; Chelliah, Pethuru Raj.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This volume constitutes peer-reviewed proceedings of the First International Conference on Data Engineering and Machine Intelligence, ICDEMI 2023. The research problems about data engineering and machine learning are covered in this book. The proceedings cover recent contributions and novel developments from researchers across industry and academia in data science, data engineering, artificial intelligence, big data, cloud computing, sustainability, and knowledge-based expert systems from technological and social perspectives. This book will serve as a valuable reference for researchers, instructors, students, scientists, engineers, managers, and industry practitioners. .
Keywords: Computational intelligence; Engineering -- Data processing; Artificial intelligence; Computational Intelligence; Data Engineering; Artificial Intelligence